Site-Selection in Single-Molecule Junction for Highly Reproducible Molecular Electronics - Kaneko, Satoshi; Murai, Daigo; Marqués-González, Santiago; Nakamura, Hisao; Komoto, Yuki; Fujii, Shintaro; Nishino, Tomoaki; Ikeda, Katsuyoshi; Tsukagoshi, Kazuhito; Kiguchi, Manabu (Journal of the American Chemical Society, 2016)
Adsorption sites of molecules critically determine the electric/photonic properties and the stability of heterogeneous molecule–metal interfaces. Then, selectivity of adsorption site is essential for development of the fields including organic electronics, catalysis, and biology. However, due to current technical limitations, site-selectivity, i.e., precise determination of the molecular adsorption site, remains a major challenge because of difficulty in precise selection of meaningful one among the sites. We have succeeded the single site-selection at a single-molecule junction by performing newly developed hybrid technique: simultaneous characterization of surface enhanced Raman scattering (SERS) and current–voltage (I–V) measurements. The I–V response of 1,4-benzenedithiol junctions reveals the existence of three metastable states arising from different adsorption sites. Notably, correlated SERS measurements show selectivity toward one of the adsorption sites: “bridge sites”. This site-selectivity represents an essential step toward the reliable integration of individual molecules on metallic surfaces. Furthermore, the hybrid spectro-electric technique reveals the dependence of the SERS intensity on the strength of the molecule–metal interaction, showing the interdependence between the optical and electronic properties in single-molecule junctions.